Aplikasi Remote Sensing dan GIS untuk Pemetaan Pengembangan Potensi Daya Tarik Wisata di Desa Pelaga Kecamatan Petang Kabupaten Badung - Firdausa, Syauqina; Lanya, Indayati; Trigunasih, Ni Made (Agrotrop : Journal on Agriculture Science, 2025)
Remote Sensing and GIS Applications for Mapping the Development of Tourist Attractions Potential in Pelaga Village, Petang District, Badung Regency. Bali is renowned for having a positive image and reputation in the tourism industry. Bali, as one of Indonesia's most popular tourist destinations, boasts rich cultural diversity, natural beauty, and rural charm. Pelaga village, for example, could be an option for the development of Bali's tourism sector, particularly in North Badung Regency, which has a carrying capacity for natural resources, agriculture, and plantations. Pelaga village itself has seven tourist attractions. The purpose of this research was to identify the degree of potential tourist attraction in Pelaga Village's tourism area, create a tourist attraction development plan, create a tourist attraction Information System, and create a map of the distribution of prospective tourist attractions in the tourist area. According to the study's findings, the standard deviation for determining the potential class in this study was 35.12774, with an average value of tourist attraction scoring of 230.57. There are two tourist attractions with great potential, three with medium potential, and two with poor potential. Tourist attractions with scores greater than 265 are classified as having high potential, those with scores between 195 and 265 as having medium potential, and those with scores less than 195 as having low potential. Remote sensing and Geographic Information System (GIS) applications can greatly improve the results of creating tourism maps. Furthermore, the technology can provide a tourism attraction information system for IT-based tourist areas.